Considerações acerca do estupro virtual - Alves Neto, Veríssimo (Universidade Federal do Tocantins, 2020)
Technology is evident nowadays and has become part of the general daily life of civilized societies to the point that the more technological is that which nowadays overlaps the other, less technological ones. Thus, amidst booming advances in tools and mechanisms that facilitate and optimize time, technology and its impulses bring with it a dangerous problem, which is the possibility of cybercrime using technology and the world that technology creates focusing this work on the analysis of the lack of correct punishment for these types of crimes. Thus, through a historical research on the development of technology, as well as a sociological approach on the development of the culture of rape, we sought to understand the nuances of cybercrime, as well as better analyze the new type of virtual sexual crime created, the cyber rape, as well as current legislation applied to it and its effectiveness. Therefore, the research is based on the dialectical methodology is the qualitative approach. In addition, as it is a little known and not doctrinally structured subject, we used the exploratory method that, initially aiming at understanding and familiarity with the theme from a bibliographic search related to the conceptual procedures adopted to study the emergence As a result of the problem, monograph research was adopted to highlight the difficulty of categorization. For such through the descriptive analysis and using the bibliographical research, the main sources chosen were scientific articles, journals, theses, dissertations, and monographs, obtained in the Google academic online platform and databases of theses and dissertations of UFSC, USP and UnB; books and the Brazilian Penal Code. The understanding that better regulation on virtual types is needed, focusing on virtual sexual crimes, which is extremely harmful to the development of contemporary technological society, but also requires better technological education as well as greater state attention. to this problem.